Opportunities of treatment for primary dysmenorrhea in young women. Case report - Nataliya A. Buralkina; Zalina K. Batyrova; Zaira K. Kumykova (IP Berlin A.V., 2021)
Primary dysmenorrhea is one of the most common causes of pelvic pain in women. It can reduce quality of life and interfere with daily activities. The use of combined oral contraceptives in young women with primary dysmenorrhea is an effective and safe treatment option. The article presents a clinical case of the effective use of combined oral contraceptives containing drospirenone in a young woman with primary dysmenorrhea and severe pain syndrome, which is not relieved by analgesics and antispasmodics and significantly reduces the patient's quality of life.